Substantial reduction in thermo-suitable microhabitat for a rainforest marsupial under climate change. (21st December 2018) - Meade, Jessica; VanDerWal, Jeremy; Storlie, Collin; Williams, Stephen; Gourret, Arnaud; Krockenberger, Andrew; Welbergen, Justin A.
Abstract : Increases in mean temperatures caused by anthropogenic climate change increase the frequency and severity of temperature extremes. Although extreme temperature events are likely to become increasingly important drivers of species' response to climate change, the impacts are poorly understood owing mainly to a lack of understanding of species' physiological responses to extreme temperatures. The physiological response of Pseudochirops archeri (green ringtail possum) to temperature extremes has been well studied, demonstrating that heterothermy is used to reduce evaporative water loss at temperatures greater than 30°C. Dehydration is likely to limit survival when animals are exposed to a critical thermal regime of ≥30°C, for ≥5 h, for ≥4 consecutive days. In this study, we use this physiological information to assess P. archeri's vulnerability to climate change. We identify areas of current thermo-suitable habitat (validated using sightings), then estimate future thermo-suitable habitat for P. archeri, under four emission scenarios. Our projections indicate that up to 86% of thermo-suitable habitat could be lost by 2085, a serious conservation concern for the species. We demonstrate the potential applicability of our approach for generating spatio-temporally explicit predictions of the vulnerability of species to extreme temperature events, providing a focus for efficient and targeted conservation and habitat restoration management.